The fertilizer industry in Cambodia: Market, challenges and the way forward - Vuthy, Theng; Pirom, Khiev; Dary, Phon (International Food Policy Research Institute, 2014)
The agricultural sector plays a crucial role in Cambodia’s economy, and accounts for approximately 27.3 percent of GDP. Crop cultiva-tion on Cambodia’s 4 million ha of agricultural land has become more challenging with each passing year due to low soil fertility (White et al., 1997). Fertilizer application is crucial for nutrient replenishment, increased crop yield and elevated crop biomass which is necessary for moisture retention and nutrient efficiency (Bumb, 1996). Cambodia expects a large proportion of improved crop produc-tion to derive from increasing crop yields, and fertilizer is expected to play a major part in meeting future demands for crop intensifica-tion and greater food security (RGC 2010).